Crystal structure of a thwarted mismatch glycosylase DNA repair complex. - Barrett, T; Schärer, O; Savva, R; Brown, T; Jiricny, J; Verdine, G; Pearl, L (1999)
The bacterial mismatch-specific uracil-DNA glycosylase (MUG) and eukaryotic thymine-DNA glycosylase (TDG) enzymes form a homologous family of DNA glycosylases that initiate base-excision repair of G:U/T mismatches. Despite low sequence homology, the MUG/TDG enzymes are structurally related to the uracil-DNA glycosylase enzymes, but have a very different mechanism for substrate recognition. We have now determined the crystal structure of the Escherichia coli MUG enzyme complexed with an oligonucleotide containing a non-hydrolysable deoxyuridine analogue mismatched with guanine, providing the first structure of an intact substrate-nucleotide productively bound to a hydrolytic DNA glycosylase. The structure of this complex explains the preference for G:U over G:T mispairs, and reveals an essentially non-specific pyrimidine-binding pocket that allows MUG/TDG enzymes to excise the alkylated base, 3, N(4)-ethenocytosine. Together with structures for the free enzyme and for an abasic-DNA product complex, the MUG-substrate analogue complex reveals the conformational changes accompanying the catalytic cycle of substrate binding, base excision and product release.